2012
DOI: 10.1177/2041731412462018
|View full text |Cite
|
Sign up to set email alerts
|

Encapsulation of factor IX–engineered mesenchymal stem cells in fibrinogen–alginate microcapsules enhances their viability and transgene secretion

Abstract: Cell microencapsulation holds significant promise as a strategy for cellular therapies; however, inadequate survival and functionality of the enclosed cells limit its application in hemophilia treatment. Here, we evaluated the use of alginate-based microcapsules to enhance the viability and transgene secretion of human cord blood–derived mesenchymal stem cells in three-dimensional cultures. Given the positive effects of extracellular matrix molecules on mesenchymal stem cell growth, we tested whether fibrinoge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
27
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 36 publications
2
27
0
Order By: Relevance
“…Similar proliferation rates have been observed with a collagen matrix [51]. In addition, proliferation of MSCs in microcapsules has generally not been observed in earlier approaches [31,45]. Transplanted MSCs perform all functions that are reported to contribute to tissue repair, as they are able to differentiate into other lineages and secrete paracrine factors.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…Similar proliferation rates have been observed with a collagen matrix [51]. In addition, proliferation of MSCs in microcapsules has generally not been observed in earlier approaches [31,45]. Transplanted MSCs perform all functions that are reported to contribute to tissue repair, as they are able to differentiate into other lineages and secrete paracrine factors.…”
Section: Discussionsupporting
confidence: 63%
“…All components are critical for the optimal performance of the microcapsule supporting proliferation and long-term survival of MSCs. Although materials such as agarose (or substituted by alginate) in combination with collagen [44], fibrin and fibronectin [30,31,45] have been investigated before, the resulting microcapsule biomaterials in earlier studies had limited performance. Most encapsulated cells (MSCs or fibroblasts) had a decreased viability over time.…”
Section: Discussionmentioning
confidence: 98%
“…Hydrogel biopolymers such as collagen, alginate, and chitosan have shown cellular compatibility and the capacity to load and carry cells to the target tissues. [5][6][7][8] Collagen can load cells and has good 1 biocompatibility, while maintaining cellular functions that mimic the native three-dimensional (3D) tissue environment. 9 Collagen also becomes a gel when pH, ionic concentration, and temperature are modulated to near biological conditions.…”
Section: Introductionmentioning
confidence: 99%
“…In past studies, sECM acted as the necessary biomechanical substrate for endogenous neuroregeneration in models of intracerebral hypoxia-ischemia and traumatic spinal cord injury, by increasing their stem cell viability and promoting differentiation into neurons (Pan, Ren, Cui, & Xu, 2009;Park, Teng, & Snyder, 2002;Teng et al, 2002). Recently, it was discovered that MSCs encapsulated in fibrinogen-alginate microcapsules possessed a significantly increased survival as compared to unencapsulated cells (Sayyar et al, 2012). In another recent study, Reagan et al demonstrated the utility of a scaffold-based delivery system for sustained therapeutic MSCs release and their ability to express genetically introduced therapeutic TRAIL.…”
Section: Encapsulated Stem Cells For Therapymentioning
confidence: 98%